2022
DOI: 10.3390/electronics11193156
|View full text |Cite
|
Sign up to set email alerts
|

Chaos-Based Cryptography: Text Encryption Using Image Algorithms

Abstract: Currently, chaotic cryptography is mainly concentrated on image encryption. Once-popular stream-encryption algorithms, e.g., textual data, are now rarely considered. This article studies how chaotic image-encryption algorithms can be used to encrypt text. The proposed approach to this problem consists of two stages: in the first stage, the text message is intended for encryption into an image; in the second step, the selected image-encryption algorithm is used. An example illustrates the efficiency of this met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Recurrent connections, which enable the network to store and process data over time, characterize the reservoir layer. In the reservoir layer, the relationships between the nodes have fixed weights, which are typically initialized arbitrarily and stay the same during training (Lawnik et al, 2022). • Output layer: The output layer produces the desired outcome or forecast using the data gathered from the reservoir layer.…”
Section: ____________________________________________________________...mentioning
confidence: 99%
“…Recurrent connections, which enable the network to store and process data over time, characterize the reservoir layer. In the reservoir layer, the relationships between the nodes have fixed weights, which are typically initialized arbitrarily and stay the same during training (Lawnik et al, 2022). • Output layer: The output layer produces the desired outcome or forecast using the data gathered from the reservoir layer.…”
Section: ____________________________________________________________...mentioning
confidence: 99%
“…The new chaotic method based on multiplicative inverse function is used to control the diffusion of block cipher by chaotic system, which enhances the performance of logistic map and has strong key sensitivity. In [39], authors revealed a text encryption method using image encryption algorithm. This method converts text to image information, and uses the existing image encryption algorithm to encrypt, providing a new train of thought.…”
Section: Plos Onementioning
confidence: 99%
“…Among them, the chaotic maps gradually become a hot research topic due to easy implementation, low cost and high complexity. In addition, they have broad application prospects in cryptography, [1,2] image encryption, [3,4] pseudorandom sequences generation, [5,6] secure communication [7,8] and other fields. [9][10][11] However, many existing chaotic maps still have limitations such as small keyspace, multiple periodic windows and weak ergodicity.…”
Section: Introductionmentioning
confidence: 99%